(untitled) (Journal of Biomedical Investigation, 2008)
The study was designed to evaluate the prevalence of HBV and HCV infections in cases referred for biochemical laboratory evaluation of liver function status. For this study, 50 serum samples with evidence of liver impairment based on biochemical evaluation and other 50 serum samples without any biochemical evidence of liver impairment, were randomly selected and called ‘impaired liver function and normal liver function groups respectively. The sera were screened for the presence of anti-HbsAg, anti-HCV and in-vivo antibody sensitization. The result of the present study showed that Anti-HbsAg was detected in 3 (6%) of the sera of normal liver function group and 5(10%) of the sera of impaired liver function group. However sensitized antibodies and anti-HCV were not present in any of the sera in both groups. The present study revealed an over all 16% prevalent rate of possible HBV infections in cases referred for biochemical evaluation of the liver function. The study showed that hepatitis B viral infection may be responsible for 1 out 10 cases of hepatitis in this area. The incidence of hepatitis B viral infection in cases of normal liver function possibly suggest that when clinical indications suspects hepatic involvement in a subject inclusion of HBV screening in addition to the normal biochemical evaluation may be necessary. The lack of evidence for HCV infection is discussed.